2018
DOI: 10.1007/5584_2018_208
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Relationship Between Phenotypic and Genotypic Resistance Profiles of Multidrug-Resistant Enterobacterial Clinical Isolates

Abstract: We suggest using blaTEM, blaCTX-M-15, qnr, and aac(6')-Ib-cr genes for better and faster prediction of suitable antibiotic therapy with effective doses against ESBL-producing isolates harboring plasmid-mediated quinolone resistance (PMQR) determinants. Amikacin, meropenem, gentamicin, and imipenem seem to be better choices of treatment for such life-threatening infections, because of their remaining highest activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
2
7
0
2
Order By: Relevance
“…In Egypt, ESBL producers are widely spread in hospitals. One recent study showed a significant association between 3rd generation cephalosporins and resistance fluoroquinolones, gentamicin and tetracycline in hospital acquired infections (Galal et al, 2018). CTX-M-1, CTX-M-9, CTX-M-15, CTX-M-14, and SHV-12 were reported in E. coli strains isolated from different clinical origins (Hassan et al, 2012; Abdelaziz et al, 2013a; Abdallah et al, 2015b; Helmy and Kashef, 2017).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…In Egypt, ESBL producers are widely spread in hospitals. One recent study showed a significant association between 3rd generation cephalosporins and resistance fluoroquinolones, gentamicin and tetracycline in hospital acquired infections (Galal et al, 2018). CTX-M-1, CTX-M-9, CTX-M-15, CTX-M-14, and SHV-12 were reported in E. coli strains isolated from different clinical origins (Hassan et al, 2012; Abdelaziz et al, 2013a; Abdallah et al, 2015b; Helmy and Kashef, 2017).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…Other ESBL producers detected in Egyptian hospitals include CTX-M-14/CTX-M-15 Enterobacter spp. (Abdallah et al, 2015b; Galal et al, 2018), CTX-M-15/SHV P. mirabilis , CTX-M-15/SHV C. freundii , CTX-M-14 Serratia marcescens (Helmy and Kashef, 2017; Galal et al, 2018) and CTX-M Salmonella spp. (Abdallah et al, 2017).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%
“…Figure 3 Summary of the prevalence (%) of ESBL-producing/third-generation cephalosporin-resistant Enterobacteriaceae (ESBL-E).Notes: Data from references27,33,42,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] . a Klebsiella spp.…”
mentioning
confidence: 99%
“…Для лечения пациентов с клебсиельными инфекциями используют беталактамные антибиотики, фторхиноло ны и аминогликозиды (Galal et al, 2019). При этом основны ми в терапии являются беталактамы, которые блокируют синтез клеточной стенки бактерий и наименее токсичны для человека.…”
Section: Introductionunclassified
“…К БЛРС относятся ферменты се мейств TEM, SHV, CTXM, OXA и др. (Gharrah et al, 2017;Galal et al, 2019). На сегодняшний день для каждого семейства беталактамаз известно большое количество аллельных вариантов, обеспечивающих устойчивость к третьему поколению цефалоспоринов, монобактамам и карбапенемам (Liakopoulos et al, 2016).…”
Section: Introductionunclassified